The Effectiveness of Digital Learning Curriculum 2013 in Pandemic - Nur, Sahril; Lakoro, Qadriyah; Lengkoan, Fergina (Journal of English Culture, Language, Literature and Education, 2023)
This paper aim to find out the effectiveness of digital learning curriculum 2013 in pandemic era. This paper is focused on how to design digital learning based on Curriculum 2013 in the middle of the COVID-19 Pandemic that is affecting all aspects of life including in part of education. In this paper, descriptive content analysis techniques and literature reviews are employed as the methodology. All of the information is obtained from scientific articles related to the material and the focus raised in this article. From the results of the analysis collected, the author reveals that although there are several advantages and disadvantages that can be obtained from online learning as we are more able to relax in carrying out activities. There are also some problems that must be faced by students and from teachers when undergoing online learning in a pandemic situation, such as validly, reliably, and long-distance communication. Based on the discussion, digital learning in curriculum 2013 can be solution to solve the problem, the advantages of digital learning such as interactive e-book, in-site and out-site classroom, creative learning, and digital literacy. The authors then concluded that teachers and students could still have to find some tools, materials, methods, and learning resources that could be used to support and facilitate students in online meetings.